Camaradas distantes: la relación entre China y la República Popular Democrática de Corea en la era del auge nuclear norcoreano. - Márdero Jiménez, Gabriela Guadalupe (El Colegio de México A.C., 2017)
China and North Korea have been allies since the foundation of the latter at the end of the 1940s. Their ideological affinity, proximity and shared history contributed to creating ties of great importance between the two countries. However, the development of the North Korea’s nuclear program together with China’s rise to occupy a global position of great importance have changed the dynamics of this relationship. This process needs to be examined with care, as historically the relationship between the two nations has transcended the bilateral sphere to have significant regional implications and is now a priority on the international security agenda.